Study on the Kinematics of Key Components of Film Bidirectional Synchronous Stretching Equipment. Issue 1 (1st December 2022) - Pan, Mingyu; Wang, Zheng
Abstract: In this paper, the stretching chain clamp model in the film synchronous biaxial stretching equipment is simplified. And we establish the kinematic model. The variation rule of kinematic parameters of each joint of the chain clamp during the film stretching process is obtained. We use ADAMS software to inverse the trajectory of the stretching chain clamp to get the theoretical track and optimize the stretching rate of the stretching chain clamp. We compare the theoretical track with the initial stretching track model, optimize of stretching system structure, and achieve reliability and stability requirements for stretching chain clamp movement. This is important for the design of the stretching system and the improvement of film stretching quality.